Description of a new species of the earthworm genus Moniligaster Perrier, 1872 (Clitellata, Moniligastridae) from the Nilgiri Biosphere Reserve of Tamil Nadu State, India - Narayanan, S. Prasanth; Ahmed, Shakoor; Thomas, A.p. (Zootaxa, 2025)
A new earthworm species, Moniligaster gatesi Ahmed & Narayanan, sp. nov., is described based on the specimens collected from Ooty in Tamil Nadu State of the Western Ghats biodiversity hotspot, India. It belongs to the gravelyi group of species, characterized by the vas deferens opening directly into the prostate, spermathecal atria confined to segment 7, and leaflet-like glands absent on the vas deferens. Among the congeners of the group, M. gatesi sp. nov. shows close similarity with M. gravelyi Stephenson, 1915, and M. bahli Narayanan & Julka, 2021. M. gatesi sp. nov. has paired atrial glands at each side, whereas the very similar-looking M. gravelyi has a single undivided atrial gland at each side. In M. gatesi sp. nov., the prostatic capsule has a shallow, nodulated surface, and the ovisacs extend in segments 13–16, but in M. bahli, the prostatic capsule is sinuous at the ental end with a few nodulations, and the ovisacs reach up to segment 20. Here we provide the detailed description of the external and internal characteristics of the new species along with the illustrations of the key characters. An updated key to the Moniligaster species is also provided.